Introducing Idioms in Foreign Language Class for Students of Translation Studies Departments of Kazakhstani Higher Institutions - Baizhanova, A.; Toleubayeva, A.; Muratova, G. (Mediterranean Journal of Social Sciences Vol 6, No 3 S2, 421 - 429, 2015)
The given article is devoted to considering the problem of using idioms in foreign language class for students of translation studies departments of Kazakhstani higher institutions. The authors analyse the current situation with teaching foreign languages for students of translation studies speciality and describe their experiment demonstrating the increase in the level of students’ motivation to learn a foreign language after introducing idioms in the class. In addition, they show the significance of mastering idioms for future translators / interpreters
Keywords: translation, interpreting teaching, foreign language teaching, motivation, idiom, idiomatology